Backbone-extended pyrrolidine peptide nucleic acids (bepPNA): design, synthesis and DNA/RNA binding studies - Govindaraju, T; Kumar, VA (Chemical Communications, 2005)
One-carbon extended conformationally constrained pyrrolidine PNA monomer (bepPNA) has been synthesized, incorporated into PNA sequences at predefined positions, and showed selective RNA binding properties.

(SR/RS)-cyclohexanyl PNAs: conformationally preorganized PNA analogues with unprecedented preference for duplex formation with RNA - Govindaraju, T; Kumar, VA; Ganesh, Krishna N. (Journal of the American Chemical Society, 2005)